May 2024 South Africa : Analysis and Perspectives - (:unkn) unknown (My University, 2024)
The seminar provided a platform for deep reflection on the progress and challenges of democracy in South Africa, urging participants to cherish and safeguard the hard-won freedoms of the nation. As South Africa approaches the elections scheduled for 29 May 2024, the seminar serves as a timely reminder of the importance of youth engagement in shaping the country’s democratic future. In her engaging discourse, Dr Severin likened South African democracy to that of “a teenager”, acknowledging the strides made since the advent of democracy in 1994. However, she astutely pointed out that despite the country boasting a robust Constitution, the pervasive issues of corruption and poverty remain significant hurdles. Drawing from her deep knowledge of the African National Congress, she shed light on the party’s overwhelming dominance in politics, which, unfortunately, provides fertile ground for corrupt practices to flourish unchecked.Throughout her presentation, Dr Severin artfully weaved in anecdotes from other African nations, such as Zimbabwe, Congo-Brazzaville, and the Democratic Republic of the Congo, where democracy has faltered.
Keywords: African Research